Development of deep leaning algorithm for multiple-input multiple-output communication system - Chen, Xingchen (Nanyang Technological University, 2022)
Multiple Input Multiple Output (MIMO) is the key technology of the fifth-generation (5G) communication technology. In order to meet the increasing communication needs of users, MIMO technology is also developing rapidly. MIMO signal detection plays a very important role in ensuring the accuracy of MIMO signal transmission. In order to further improve the signal detection accuracy and efficiency of MIMO system, people try to design MIMO system detector by using machine learning.